2020
DOI: 10.1080/21645515.2020.1807812
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of newborn hepatitis B immunization in Beijing

Abstract: Objectives To evaluate cost-utility of universal Hepatitis B vaccination program in the Beijing city (Beijing). Methods A decision-Markov model was constructed to determine the cost-utility of the universal immunization program for infants (universal vaccination program) by comparing with a hypothetic nonvaccination strategy in Beijing. Parameters in models were extracted from Beijing Center for Disease Control and Prevention (CDC) annual work report, Beijing health sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…We observed differing hepatitis B vaccination coverage rates among different household registration. A reason for this may be that Beijing was among the first few cities to implement a hepatitis B vaccination policy for newborns since 1992 [16], and Beijing has higher medical resources and better health education compared to other cities. Individuals with confirmed or suspected family cases or knowledge of hepatitis B vaccination had high vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed differing hepatitis B vaccination coverage rates among different household registration. A reason for this may be that Beijing was among the first few cities to implement a hepatitis B vaccination policy for newborns since 1992 [16], and Beijing has higher medical resources and better health education compared to other cities. Individuals with confirmed or suspected family cases or knowledge of hepatitis B vaccination had high vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that Beijing's current vaccination program could significantly reduce the economic burden of HBV-related disease [16]. Here, we aimed to perform a cross-sectional study to explore hepatitis B vaccination coverage rates and related factors among the general population of Beijing for future vaccination strategies.…”
Section: Introductionmentioning
confidence: 99%
“…39 But in a high vaccine coverage country, the current model is probably sufficient. 20,40 Furthermore, the transition prob- In conclusion, this economic evaluation suggests that the PVST strategy is a more cost-effective choice for infants born to HBsAgpositive mothers than the current strategy. Health policy makers may consider to further promote the PVST projects to protect more high-risk infants.…”
Section: Discussionmentioning
confidence: 87%
“…Secondly, squaring up to the impact of herd immunity and that the protection of the HBV vaccine would weaken by age, 38 a dynamic model might be considered more realistic in this study 39 . But in a high vaccine coverage country, the current model is probably sufficient 20,40 . Furthermore, the transition probabilities were primarily derived from published literatures, mainly from China and Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…In China, the cost-utility model of the universal vaccination program in 2016 determined a saving of US$3779.16 per quality-adjusted life years (QALY) with universal vaccination compared with non-vaccination and prevented 18,322.25 QALY due to hepatitis B-related complications. This resulted in an estimated saving of US$347,962,414.43 over the lifespan of the target cohort [ 73 ]. Using Taiwanese data, Markov modelling demonstrated that universal vaccination led to societal cost savings of NT$55,201 per year and healthcare-associated cost savings of NT$23,830 per year by reducing long term complications associated with chronic hepatitis B, including HCC [ 74 ].…”
Section: Cost-effectiveness Of Hepatitis B Vaccination For Prevention...mentioning
confidence: 99%